A contribuição da governança na criação de valor público em municípios de pequeno porte na perspectiva de cidades inteligentes e sustentáveis: um estudo de caso Na política pública de saúde - Linhares, João Eduardo (2023)
This thesis aimed to understand how governance can contribute to creating public value in small municipalities, with the goal of fostering the development of smart and sustainable cities. The study was based on a systematic literature review and a case study in a Brazilian municipality. The systematic review selected 57 relevant articles using the Knowledge Development Process-Constructivist (PROKNOW-C) method, which contributed to the bibliometric analysis, highlighting the main authors, countries of origin of research, keywords, and relevant journals in the field. Furthermore, the systemic analysis identified issues such as the scope of research, various concepts related to governance, theoretical models of governance, the relationship between governance and smart and sustainable cities, as well as existing research gaps. Few studies in the portfolio addressed the governance of smart and sustainable cities in developing countries, primarily in small municipalities. Furthermore, there was a need to advance research on regional governance in the context of smart cities, as well as in understanding the creation of public value and its relationship with the governance of small municipalities. In the case study, governance practices in the public health policy of São Lourenço do Oeste, a small municipality in Brazil, were investigated, with a focus on promoting the development of smart and sustainable cities through their institutional arrangements and the public value generated. To conduct the case study, qualitative and quantitative methods were used, including documentary and bibliographical research, semi-structured interviews, content analysis, and secondary data analysis. The results demonstrated the municipality's ability to coordinate itself through institutional arrangements, incorporating smart, data-driven, urban, smart urban, regional, and technocratic governance approaches. The results of the interviews and the analysis of indicators of SUS outpatient production for São Lourenço do Oeste, which demonstrated the evolution of health results between 2008 and 2022, are associated with the municipality's ability to create public value, bringing numerous benefits to the population. The case study highlighted the relationship between contextual conditions, governance practices, and the creation of public value with the dimensions of smart and sustainable cities. The research model was essential for understanding health policies in complex and challenging environments. Municipal governance, through regional arrangements and participation in the SUS, has shown effectiveness in creating public value, validated by perceptions and indicators of access to health. This highlighted the importance of governance and creating public value for the development of smart and sustainable cities. Small municipalities play a crucial role in creating public value in health, emphasizing innovation with ICT, collaboration in decision-making, and participation in regional arrangements. The regional governance of the SUS, with decentralization and consortia, are action strategies that seek to guide management towards sustainable development. This thesis is a valuable resource to guide future research and management actions in health, highlighting the relevance of governance in creating public value in small municipalities.